Autoimmunity linked protein phosphatase PTPN22 as a target for cancer immunotherapy. Issue 2 (30th October 2020) - Cubas, Rafael; Khan, Zia; Gong, Qian; Moskalenko, Marina; Xiong, Huizhong; Ou, Qinglin; Pai, Christine; Rodriguez, Ryan; Cheung, Jeanne; Chan, Andrew C
Abstract : Background: Cancer immunotherapy has evolved from interferon-alpha (IFNα) and interleukin-2 in the 1980s to CTLA-4 and PD-1/PD-L1 checkpoint inhibitors (CPIs), the latter highlighting the importance of enhancing T-cell functions. While the search for novel immunomodulatory pathways continues, combination therapies augmenting multiple pathways can also increase efficacy. The association of autoimmune-related adverse events with clinical efficacy following CPI treatment has been inferred and suggests that breaking tolerance thresholds associated with autoimmunity may affect host immune responses for effective cancer immunotherapy. Results: Here, we show that loss of autoimmune associated PTPN22, a key desensitization node for multiple signaling pathways, including IFNα receptor (IFNAR) and T-cell receptor, can augment tumor responses. Implantation of syngeneic tumors in Ptpn22 -/- mice led to expansion and activation of peripheral and intratumoral T cells and, in turn, spontaneous tumor regression as well as enhanced responses in combination with anti-PD-L1 treatment. Using genetically modified mice expressing a catalytically inactive PTPN22 or the autoimmunity-associated human single-nucleotide polymorphism variant, augmentation of antitumor immunity was dependent on PTPN22 phosphatase activity and partially on its adaptor functions. Further, antitumor responses were dependent on both CD4 + and CD8 + T cells and, in part, IFNAR function. Finally, we demonstrate that the autoimmune susceptibility Ptpn22(C1858T ) variant is associated with lower risk of developing non-melanoma skin cancers, improved overall survival and increased risk for development of hyperthyroidism or hypothyroidism following atezolizumab (anti-PD-L1) treatment. Conclusions: Together, these data suggest that inhibition of PTPN22 phosphatase activity may provide an effective therapeutic option for cancer immunotherapy and that exploring genetic variants that shift immune tolerance thresholds may serve as a paradigm for finding new cancer immunotherapy targets.